القيمة التربوية المضمونة في معاني أسلوب الاستفهام عند سورة البقرة - Komalasari, Nunung (STAINI Press, 2022)
This research aims to analyze the verses of the Qur'an that use interrogative style and researching its relationship with educational values that are common in Indonesian culture and educational values in Islam. In this research the researcher reveals the meanings of interrogative sentences that used in the verses which means figure of speech (connotative). In this research, researcher used qualitative method, while the technique used in writing this research is an analytical technique from the point of view of education and describes it deductively. The interrogative style is one of the language styles insya’ thalabiy that exists in the study of balaghah science directly and indirectly, and the discussion about the structure of the interrogative sentence can go beyond its original meaning in balaghah (asking for information about something that is not known), and sometimes the meaning is intended to show another meaning in a figurative way with the differences of opinion between the Balaghah experts or the Mufassirs.. And the results of this research, it is known that in surah al-Baqarah there are many interrogative verses that contain educational values, and most of them contain social educational value, religious educational value, and the moral educational value,